Atividade física durante a gestação em ratas alimentadas com dieta de cafeteria promove proteção hepática na prole aos 21 dias - Bueno, Giselle Cristina (2014)
Studies have shown that the use of hypercaloric diets during pregnancy and lactation in rats may cause deleterious effects not only to genitors but also their offspring, with the onset of metabolic and cardiovascular disorders in adulthood. Such evidence leads us to the question whether the insertion of physical activity during pregnancy can prevent or at least minimize the deleterious effects of maternal diet on offspring at weaning. Thus the aim of the study was to evaluate the effect of cafeteria diet and physical activity during pregnancy on hepatic fatty infiltration and muscle morphology in offspring of rats after weaning. To constitute the experimental groups pregnant female Wistar rats, 70 days old, were fed a chow or cafeteria diet and submitted to a treadmill light physical exercise during 18 days, avoiding the last 3 days of gestation. After birth, only the cafeteria diet was kept and the following groups randomly assigned: Offspring of sedentary control (SC), offspring of trained control (TC), offspring of sedentary cafeteria (CaS) and offspring of trained cafeteria (CaT). After the end of the weaning period, 21 days,8 hours fasting pups were anesthetized and caudal blood collected to determine glycemia using a glucometer. Soon after, the animals were euthanized and blood, liver and gastrocnemius muscle excised. The histochemical techniques Sudan III and hematoxylin and eosin (HE), respectively, were employed for evaluation of fatty infiltration and muscle area. The dosage of the enzymes aspartate aminotransferase (AST) and alanine aminotransferase (ALT) and creatine kinase (CK) were used as markers of liver and muscleinjury, respectively. As a result it was observed that the cafeteria diet during gestation and lactation induced liver damage in the offspring at weaning, evidenced by increased accumulation of lipid infiltration and increases in the concentrations of AST and ALT. On the other hand, physical activity was able to reduce the level of infiltration. No differences were observed in gastrocnemius muscle fiber area, but both diet and physical activity increased CK levels. In summary, we conclude that physical activity during pregnancy was efficient to mitigate the deleterious effects of diet on lipid infiltration, since the exercise groups presented lower values of infiltration area compared with thecontrol groups at weaning.